2018
DOI: 10.16899/gopctd.414435
|View full text |Cite
|
Sign up to set email alerts
|

Psikiyatrik Hasta Popülasyonunda Beden Kitle İndeksi ve İlişkili Faktörler

Abstract: Psikiyatrik hastalıklar ve beden kitle indeksi ilişkisi Relation of body mass index and psychiatric disorders Amaç: Obezitenin, Dünya Sağlık Örgütü'nün (WHO) yaptığı çalışmalarla, ABD ve Avrupa ülkeleri başta olmak üzere Türkiye'de de görülme sıklığının arttığı ve bir halk sağlığı sorunu haline geldiği ortaya konmuştur. Günümüz yaşam koşullarında ruh hastalıkları da küresel anlamda giderek artan bir oranda toplumları etkilemektedir. Bu çalışmada obezitenin sınıflandırılmasında kullanılan beden kitle indeksinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
2
0
1
Order By: Relevance
“…Tashakori et al, 43 in their study where they examined the relationship between BMI and depression, stated that individuals who were slightly obese (25BMI < 30) experienced moderate depression and individuals who were obese (BMI>30) experienced major depression. [40][41][42][43] This finding obtained in the study is similar to the findings made before the pandemic.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Tashakori et al, 43 in their study where they examined the relationship between BMI and depression, stated that individuals who were slightly obese (25BMI < 30) experienced moderate depression and individuals who were obese (BMI>30) experienced major depression. [40][41][42][43] This finding obtained in the study is similar to the findings made before the pandemic.…”
Section: Discussionsupporting
confidence: 87%
“…Khan et al 40 stated that there was a positive and statistically significant relationship between BMI and major depression in the study in which they examined the relationship between major depression and BMI. Pahali et al, 41 in their study where they examined the relationship between psychiatric diseases and BMI, stated that the mean score of depression scale was higher than other individuals and that there was a statistically significant relationship between BMI and depression score. Dolatian et al, 42 in their study where they examined the relationship between BMI and depression, stated that individuals with BMI 25 and above had a higher mean depression score than those with BMI below 25.…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmalar, depresyon seviyesinin ve obezitenin birbiriyle etkileşim halinde olduğunu ve majör depresyonda olan bireylerin yüksek enerji alımına bağlı olarak obezite oluşum riskinin artmış olabileceğini göstermiştir (26,27). Yapılan çalışmalar, stres ile besin alımı arasındaki potansiyel ilişkileri ortaya koymaktadır.…”
Section: Discussionunclassified
“…There is not much knowledge and findings about the relationship between depression and body composition (Speed, Jefsen, Børglum, Speed, & Østergaard, 2019); generally, the relationship between BMI and depression has been emphasized in existing studies (Pahalı, Omay, Bulut, & Sayar, 2018). However, in their study Speed et al (2019), reported that although BMI was a risk factor for depression, it did not differentiate between fat mass and lean body mass and the BMI-depression causation was driven by fat.…”
Section: Dıscussıonmentioning
confidence: 96%